Analysis of reinforced concrete beams strengthened with different CFRP lengths - Silva, Ricardo José Carvalho (2019)
The application of carbon fiber reinforced polymers (CFRP) as method of strengthening for concrete structures is replacing the conventional strengthening through the bonding of steel plates. However, since it is a recent technique, several codes from different countries still do not consider this type of strengthening. In this work, seven reinforced concrete beams were tested and analyzed. One was used as a reference beam and six were strengthened through the application of CFRP, with some variations regarding the strengthening, with the aim of verifying the efficiency of each system compared to the reference beam. For the computational analysis, the software ANSYS was used along with the plugin ACP (ANSYS Composite PrepPost), by comparing the results obtained in the simulation of the experimental results. Through the laboratory tests and the finite element simulation, it was concluded that the strengthening was efficient in all situations, but it was less efficient in cases where the strengthening was extended to the regions of simple flexure without proper anchorage. It was also possible to notice that the behavior of the simulated beams properly represented the reality, with the beams behaving comparably to the beams of the experimental test.